Near-threshold H/D exchange in CD₃CHO photodissociation. - Heazlewood, B; Maccarone, A; Andrews, D; Osborn, D; Harding, L; Klippenstein, S; Jordan, M; Kable, S (2011)
Measuring the isotopic abundance of hydrogen versus deuterium atoms is a key method for interrogating reaction pathways in chemistry. H/D 'scrambling' is the intramolecular rearrangement of labile isotopes of hydrogen atoms and when it occurs through unanticipated pathways can complicate the interpretation of such experiments. Here, we investigate H/D scrambling in acetaldehyde at the energetic threshold for breaking the formyl C-H bond and reveal an unexpected unimolecular mechanism. Laser photolysis experiments of CD₃CHO show that up to 17% of the products have undergone H/D exchange to give CD₂H + DCO. Transition-state theory calculations reveal that the dominant mechanism involves four sequential H- or D-shifts to form CD₂HCDO, which then undergoes conventional C-C bond cleavage. At the lowest energy the molecule undergoes an average of 20 H- or D-shifts before products are formed, evincing significant scrambling of H and D atoms. Analogous photochemically induced isomerizations and isotope scrambling are probably important in both atmospheric chemistry and combustion reactions.